Spatial monitoring of land surface temperature and solar radiation energy using remote sensing data and geo statistics (Case study: Lut desert) - Mohsen Pourkhosravani; Ali Mehrabi; Behnaz shaikhshariati (تحقیقات کاربردی علوم جغرافیایی)
Solar energy is receiving lots of attention because it is one of the cleanest, cheapest and most available energies in the world.but solar radiation in different parts is changing, thus, identifying appropriate locations for implementation of solar energy is necessary. Accordingly the aim of this study was to analyze the potential of solar radiation and land surface temperature on the Loot desert using remote sensing and geo statistical technique. Results show that Earth's surface temperature fluctuates between 29 and 79 degrees Celsius in the Lut Plain. So that Earth's temperature increases to the east and north-east of the region. Also, the radiation energy reaching the surface in the Lut plain varies from 232.77 to 237.61w/m² in different parts of the Lut plain. So that the maximum amount of energy is related to the south of the plain, and the further we move to the north reduces the amount of energy.